2021
DOI: 10.1007/s10669-021-09813-3
|View full text |Cite
|
Sign up to set email alerts
|

Native populations and the opioid crisis: forging a path to recovery

Abstract: American Indian/Alaska Native (AI/AN) populations have proven particularly susceptible to the opioid crisis in the USA, but the White House’s 2019 national opioid policy roadmap is not structured to address AI/AN vulnerabilities. The concept of resilience, usually considered a positive system attribute, can be applied to complex systems to understand the larger compensatory interactions that restore systems to previous structures despite disruptions or interventions. The opioid crisis is a case of detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The Native American respondents in this study claimed that they never had problems with substances or received treatment. This would not be representative of the larger Native American population, as endless studies and practical work in clinical settings have consistently shown that this population has among the highest rates of substance use/abuse and deaths from overdose (e.g., Running Bear et al, 2017;Soto et al, 2022;Whelshula et al, 2021). Further research focusing entirely on Native Americans and use/abuse of substances and treatment is clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The Native American respondents in this study claimed that they never had problems with substances or received treatment. This would not be representative of the larger Native American population, as endless studies and practical work in clinical settings have consistently shown that this population has among the highest rates of substance use/abuse and deaths from overdose (e.g., Running Bear et al, 2017;Soto et al, 2022;Whelshula et al, 2021). Further research focusing entirely on Native Americans and use/abuse of substances and treatment is clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Structural racism, including poor working conditions, lack of economic opportunities, and limited social capital in communities, are the primary drivers of opioid misuse ( 7 ). These factors, coupled with unregulated opioid prescribing practices, systemic issues with healthcare facilities and health service delivery in Indian country, and unfair marketing practices targeting AI/AN populations, have resulted in a significant drug crisis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…How do we stop opioid abuse in tribal communities? (28) In my experience as a Tribal Attorney for 10 years, it often comes in the form of providing consequences to those abusing drugs. Consequences include going to jail, the removal of children, job loss, and being ordered to attend treatment.…”
mentioning
confidence: 99%
“…If abusers are not able to get out of the cycle of addiction they will likely end up in jail, or overdose, or end up dead. However, even when people want to get clean and sober the continuing challenges of finding employment, housing and accessing outpatient treatment programs can be significant barriers (28). However, we are now seeing illicit opioids like heroin becoming more accessible.…”
mentioning
confidence: 99%